2015
DOI: 10.3389/fphar.2015.00250
|View full text |Cite
|
Sign up to set email alerts
|

Supramammillary serotonin reduction alters place learning and concomitant hippocampal, septal, and supramammillar theta activity in a Morris water maze

Abstract: Hippocampal theta activity is related to spatial information processing, and high-frequency theta activity, in particular, has been linked to efficient spatial memory performance. Theta activity is regulated by the synchronizing ascending system (SAS), which includes mesencephalic and diencephalic relays. The supramamillary nucleus (SUMn) is located between the reticularis pontis oralis and the medial septum (MS), in close relation with the posterior hypothalamic nucleus (PHn), all of which are part of this as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…The present data suggest that this partial rescue is likely to be independent of HPCxSuM theta coherence, given coherence/PPC in the REG condition is statistically indistinguishable from TET and IRR and much lower than CON and BP. Additionally, SuM theta PSD was also found to be uncoupled to water maze learning (i.e., lowest in REG and equivalent to CON in TET and IRR), suggesting water maze learning may also be relatively independent of SuM theta oscillations, despite reported experience-dependent changes (Ruan et al, 2011 ; Hernandez-Perez et al, 2015 ). While SuM inactivation moderately impairs water maze learning in single-day (Pan and McNaughton, 1997 ) or multi-day (Shahidi et al, 2004 ) versions of the task, lesion of SuM does not appear to affect water maze learning in the multi-day version of the task (Pan and McNaughton, 2002 ; Aranda et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data suggest that this partial rescue is likely to be independent of HPCxSuM theta coherence, given coherence/PPC in the REG condition is statistically indistinguishable from TET and IRR and much lower than CON and BP. Additionally, SuM theta PSD was also found to be uncoupled to water maze learning (i.e., lowest in REG and equivalent to CON in TET and IRR), suggesting water maze learning may also be relatively independent of SuM theta oscillations, despite reported experience-dependent changes (Ruan et al, 2011 ; Hernandez-Perez et al, 2015 ). While SuM inactivation moderately impairs water maze learning in single-day (Pan and McNaughton, 1997 ) or multi-day (Shahidi et al, 2004 ) versions of the task, lesion of SuM does not appear to affect water maze learning in the multi-day version of the task (Pan and McNaughton, 2002 ; Aranda et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that SuM integrity is not always necessary for HPC theta to occur (Thinschmidt et al, 1995 ) and may merely reduce peak frequency in the freely moving rat (McNaughton et al, 1995 ). More recent data based on spike-field Granger causality have suggested a role for the SuM in modulating HPC theta at higher frequencies (Kocsis and Kaminski, 2006 ), which is related to water maze learning/performance (McNaughton et al, 2006 ; Ruan et al, 2011 ; Hernandez-Perez et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Morris water maze (DMS-2 type, produced by the Institute of Materia Medica, Chinese Academy of Medical Sciences) was used before and after drug treatment to detect changes in cognitive function [6]. The test consisted of two parts: a place navigation and spatial probe test.…”
Section: Methodsmentioning
confidence: 99%
“…Theta is well understood both in terms of its underlying physiology and its potential function (for reviews, see Buzsáki, 2002;Dickson et al, 2000;Vinogradova, 1995). Functionally, theta is attributed with supporting navigation (Blair et al, 2007;Brandon et al, 2011;Burgess et al, 2007;Newman and Hasselmo, 2014;Onslow et al, 2014), mediating associational learning (Caplan et al, 2003;Hasselmo et al, 2002;Hernández-Pérez et al, 2015;2016;Honey et al, 2017;Muller et al, 2018;Norman et al, 2006;Patel et al, 2012), and pacing the relative timing of the distinct components of the entorhinal-hippocampal circuit (Mizuseki et al, 2009). These proposed functions are not mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%